The effect of iron tablet consumption monitoring cards on increasing hemoglobin levels in female adolescents - Linda, Delvina Roswita; Noftalina, Elsa; Rosita, Desy (ELECTRON (Journal of Science and Technology), 2025)
Anemia in adolescent girls (rematri) is a serious health problem that affects academic performance and increases the risk of anemia during pregnancy, potentially disrupting fetal growth and development. The government is trying to address this by providing iron tablets to all adolescent girls to meet their iron intake. This study aims to analyze the effect of using iron tablet consumption monitoring cards on increasing hemoglobin levels in adolescent girls at SMPN 03 Sadaniang, Mempawah Regency. This study used a quantitative approach with a pre-experimental method and a pre- and post-test design without a control group. The sampling technique used was total sampling on 31 adolescent girls. The results showed an increase in hemoglobin levels after the intervention. Before the treatment, the respondents' hemoglobin levels ranged from 7.9 mg/dl to 11.8 mg/dl, with an average of 11 g/dl. After the intervention using the monitoring card, hemoglobin levels increased to 11.2 g/dl to 14.1 g/dl, with an average of 12.91 g/dl. It was concluded that there was a significant effect of the use of iron tablet consumption monitoring cards on the increase in hemoglobin levels among female students at SMPN 03 Sadaniang, Mempawah Regency.